Capital Market Access, Alternative Financial Inclusion, and Small Business Performance: An Sem Study of Small Business Actors in East Jakarta - Adityawarman Sumanto; Dzuriyatun Toyibah; Ahmad Abrori (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This article analyzes the influence of the capital market on small business actors in East Jakarta using a Partial Least Squares-based Structural Equation Modeling (PLS-SEM) approach. The study focuses on five constructs: capital market literacy, capital market access/participation, business investment readiness, alternative financial inclusion, and small business performance. The quantitative data used in this article are simulated survey data from 220 small business actors in East Jakarta using a 1-5 Likert scale; the data were prepared to provide an example of an SEM analysis design and must be replaced with field data if the article is to be published as empirical research. The test results show that capital market literacy has a positive effect on capital market access/participation (β = 0.513; p < 0.001) and business investment readiness (β = 0.516; p < 0.001). Capital market access/participation and business investment readiness also have positive effects on alternative financial inclusion, while alternative financial inclusion is the strongest predictor of small business performance (β = 0.318; p < 0.001). These findings affirm that the capital market should not only be understood as an investment facility for large companies, but also as an ecosystem of financing, literacy, networking, and governance discipline that can strengthen the competitiveness of small businesses. The article recommends strengthening community-based capital market education for small businesses, assisting business actors in preparing financial reports, expanding access to securities crowdfunding, and integrating capital market programs with regional small business empowerment policies.